Diabetes Mellitus and systemic arterial hypertension: a study among primary care adults users (Brazilian Journal of Health Research, 2022)
Introduction:Diabetes Mellitus and systemic arterial hypertension are chronic metabolic disorders that culminate in several health problems, and the identification of their main risk factors is fundamental for the achievement of a better education of the population. Objectives: To estimate the prevalence of diabetes mellitus and systemic arterial hypertension, and to verify the association of these diseases with socioeconomic, behavioral, and clinical factors. Methods: Cross-sectional study, carried out in 26 health units in the city of Vitória - ES, where 991 women aged 20 to 59 years were interviewed. Statistical data analysis was performed using the Stata 13.0 program using Pearson’s Chi Square test for bivariate analysis and Poisson regression for the multivariate. Results: The prevalence of hypertension was 21,9% and diabetes was 8,2%, being higher among women aged 50 to 59 years and among those who had up to four years of study. Still, having a clinical diagnosis for one of the diseases studied, increased the prevalence of the other. Among hypertensive women, 52,0% were self-declared black and those with menarche less than or equal to 11 years of age had 1,65 times (95% CI: 1,23-2,19) more prevalence of HAS. Conclusion: The recognition of risk factors contributes to the direction of health actions, allowing the minimization of aggravating events caused by chronic diseases. The development of further studies on the relationship between early menarche and the development of hypertension should be considered.
Keywords: Diabetes mellitus; Hypertension; Primary health care; Epidemiology